Collection of photographs relating to Papua and New Guinea Territory - Australian National University. Pacific Manuscripts Bureau (Canberra : Pacific Manuscripts Bureau, 1968)
The collection consists of two series of photographs. In the first series of 10 large-size photos, numbers 1-6 are of natives of Manus Province and numbers 7-10 are from the Baining and Tolai areas of East New Britain. The photos illustrate native dress, dance dress and masks, customs and housing. The second series consists of 176 smaller photos mostly taken in or around Rabaul, Kokopo, Port Moresby and Samarai in Milne Bay. A numbered list precedes the set with brief information on each photo. Included are photos of white soldiers; natives; landscapes; Commander Col. S.A. Pethebridge, Admistrator from Jan. 1915 to Oct. 1917; and local buildings giving a good impression of the state of these places when they were taken over by the Australians. The two series are preceded by detailed notes on the photos compiled by Mr Ton Otto, Department of Anthropology, Research School of Pacific Studies who has also provided a list of related literature.
Microfilm copy of originals held in private ownership.
The origin of the photographs is unknown however, they have been identified as being from the Manus Province, possibly Manus Island, and from the Baining and Tolai areas of east New Britain.
Keywords: Pethebridge, S. A. -- Photographs; Housing -- Papua New Guinea -- Photographs; Soldiers -- Papua New Guinea -- Photographs; Port Moresby (Papua New Guinea) -- Photographs; Rabaul (Papua New Guinea) -- Photographs; Manus Province (Papua New Guinea) -- Social life and customs; New Britain Island (Papua New Guinea) -- Social life and customs